Moderate phosphorus additions consistently affect community composition of arbuscular mycorrhizal fungi in tropical montane forests in southern Ecuador. Issue 5 (1st June 2020) - Dueñas, Juan F.; Camenzind, Tessa; Roy, Julien; Hempel, Stefan; Homeier, Jürgen; Suárez, Juan Pablo; Rillig, Matthias C.
Summary: Anthropogenic atmospheric deposition can increase nutrient supply in the most remote ecosystems, potentially affecting soil biodiversity. Arbuscular mycorrhizal fungal (AMF) communities rapidly respond to simulated soil eutrophication in tropical forests. Yet the limited spatio‐temporal extent of such manipulations, together with the often unrealistically high fertilization rates employed, impedes generalization of such responses. We sequenced mixed root AMF communities within a seven year‐long fully factorial nitrogen (N) and phosphorus (P) addition experiment, replicated at three tropical montane forests in southern Ecuador with differing environmental characteristics. We hypothesized: strong shifts in community composition and species richness after long‐term fertilization, site‐ and clade‐specific responses to N vs P additions depending on local soil fertility and clade life history traits respectively. Fertilization consistently shifted AMF community composition across sites, but only reduced richness of Glomeraceae. Compositional changes were mainly driven by increases in P supply while richness reductions were observed only after combined N and P additions. We conclude that moderate increases of N and P exert a mild but consistent effect on tropical AMF communities. To predict the consequences of these shifts, current results need to be supplemented with experiments that characterize local species‐specific AMF functionality.